Managing refuse-derived and solid recovered fuels - European Investment Bank (European Investment Bank, 2024)
Waste treatment practices generate left-over materials, including refused-derived fuels, which need to be managed effectively to meet the European Union’s ambitious circular economy targets, especially regarding landfilling.This study identifies key considerations for the use of refuse-derived fuels and solid recovered fuels in energy-intensive industrial processes and shows that the use of these fuels could be a viable option for reducing landfilling in several EU countries.The report aims to raise awareness and inspire project-specific studies to help waste plant operators, designers, engineers and managing authorities identify and further explore options for their specific projects.